2021
DOI: 10.12659/ajcr.931321
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation Improved Acute Anterior Uveitis of 3-Year Duration: A Case Report

Abstract: Patient: Female, 18-year-old Final Diagnosis: Autoimmune uveitis Symptoms: Anterior phlogosis • recurrent eye redness Medication: — Clinical Procedure: Best-corrected visual acuity • fundus examination • intraocular pressure measurment • slit lamp examination • spectral domain OCT (SD-OCT) Specialty: Ophthalmology Objective: Unusual setting of medical care Background: Uveitis is a clinical condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…She was successfully treated with dietary probiotic and steroids. The possible explanation is that gut dysbiosis can influence the prognosis of uveitis by inducing a loss of the gut's immune homeostasis, thus promoting inflammation [15]. The results of this study are consistent with another case report.…”
Section: Discussionsupporting
confidence: 91%
“…She was successfully treated with dietary probiotic and steroids. The possible explanation is that gut dysbiosis can influence the prognosis of uveitis by inducing a loss of the gut's immune homeostasis, thus promoting inflammation [15]. The results of this study are consistent with another case report.…”
Section: Discussionsupporting
confidence: 91%
“…In humans, data obtained from a case report conducted on a 21-year-old woman affected by refractory acute anterior uveitis showed that combining steroids with probiotics improves visual acuity and limits ocular inflammation [207]. While in this study a probiotic mixture composed of Bifidobacterium bifidum, Bifidobacterium lactis, and Bifidobacterium breve was used [207], the potential of using other probiotic formulations as therapeutic treatment for uveitis remains to be investigated. ↓ Acellular capillaries (retina) ↓ TNF-α, ICAM-1, MCP-1, IL-1α (retina) [212] Ang Daily for 1 month ↓ Dry eye ↑ Intestinal homeostasis [198] Abbreviations: ACE2: angiotensin-converting enzyme Additional evidence on the immunomodulatory potential of probiotics comes from two independent prospective comparative pilot studies carried out in 20 adults and 26 children with chalaziosis.…”
Section: Probioticsmentioning
confidence: 90%
“…Based on these advantages, probiotics have been considered a potential treatment for various diseases associated with GM dysbiosis, including intestinal bowel syndrome, ulcerative colitis, rheumatoid arthritis, major depressive disorder, and even cancer [189][190][191][192]. Although in the context of eye disorders the evidence remains scarce, results from preclinical studies are promising, and preliminary data coming from human studies are encouraging the design of further clinical trials [193][194][195][196] (Table 1) [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213]. There is evidence that mice with ocular inflammation receiving eye drops containing the cell-free supernatant of the probiotic Lactiplantibacillus plantarum show reduced ocular inflammation, lower amount of infiltrating inflammatory cells, and diminished levels of the pro-inflammatory cytokines TNF-α and IFN-γ [205].…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation